Nutritional status in subacute post-stroke patients undergoing rehabilitation treatment: a protocol for a prospective observational study - Mariacristina Siotto; Carola Cocco; Alessandro Guerrini; Chiara Bertoncini; Marco Germanotta; Valeria Cipollini; Laura Cortellini; Arianna Pavan; Stefania Lattanzi; Caterina Galluccio; Sabina Insalaco; Erika Antonacci; et al. (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Recent developments in clinical nutrition emphasise the value of early intervention and proper nutritional management and the significance of a multidisciplinary approach to the treatment of post-stroke patients. A recent study by our research group demonstrated the correlation between nutritional status and recovery in post-stroke patients during rehabilitation. This protocol aims to examine and delineate in detail the nutritional status of subacute post-stroke patients before and after the rehabilitation treatment. Methods This clinical study is a monocentric prospective longitudinal observational research project. The aim of the protocol described herein is to assess the nutritional status, both on admission (T0) and after six weeks of rehabilitation treatment (T1), in a cohort of subacute stroke patients. In addition to clinical evaluations, we will determine anthropometric measurements, malnutrition will be diagnosed as for Global Leadership Initiative on Malnutrition (GLIM) criteria, and food intake will be registered combined with bromatological analysis. Bioelectrical impedance analysis (BIA) will be conducted to evaluate body composition, while sarcopenia will be diagnosed following the European Working Group on Sarcopenia in Older People (EWGSOP2) guidelines. Metabolic status will be assessed through indirect calorimetry and haematochemical analyses. As a secondary outcome, the correlation between the aforementioned assessments and rehabilitation outcomes will be examined. Discussion This document outlines the protocol “Nutritional Status in Subacute Stroke Patients Undergoing Rehabilitation”, which aims to assess rigorously and more specifically the nutritional status. The advantage of this study is that nutritional assessment will include numerous instrumental and biological analyses, providing a comprehensive and exhaustive assessment of patients’ nutritional status on admission and after six weeks of rehabilitation. This will provide information about the correct assessment and monitoring of the nutritional status of post-stroke patients during hospitalization for rehabilitation. It is of utmost importance to avoid the increasing risk of complications associated with undiagnosed malnutrition and sarcopenia during the months of hospitalisation for rehabilitation. Trial registration number NCT06096350 (ClinicalTrials.gov), date of registration: 23/10/2023.